การศึกษามุมมองของครูสอนภาษาอังกฤษต่อการใช้ดนตรีในการสอนภาษาอังกฤษในโรงเรียนมัธยมศึกษาในประเทศไทย - ซี เซียว เว่ย; โหมดหิรัญ ปราณภา (An Online Journal of Education, 2015)
The present study aimed to 1) investigate English teachers’ perspectives on using music in English teaching in Thai secondary schools and 2) explore the problems the teachers met while using music in teaching English in Thai secondary schools. Participants in the study were 55 English teachers from Thai secondary schools. The research instrument was a questionnaire which included 24 Likert-scale items asking about teachers’ perspectives including the attitudes, beliefs, intentions and problems of using music in English teaching, and one open-ended question asking about the problems the teachers met while using music in their English teaching. The findings from the quantitative data revealed the positive attitudes and beliefs of the English teachers in Thai secondary schools on using music in English teaching; in the findings from the open-ended content analysis mismatched with the teachers’ attitudes and beliefs that teachers actually did not use music in their English teaching frequently. The problems reported by the participants included 1) the inappropriateness of language uses in music; and 2) the lack of experience and relevant training on using music in English teaching.